Malaysian corporate tax rate and revenue: the application of Ibn Khaldun tax theory - Annuar, Hairul Azlan; Isa, Khadijah; Ibrahim Aramide, Salihu; Solarin, Sakiru Adebola (Emerald Publishing Limited, 2018)
Purpose – The present study aims to investigate the impact of the reduction of the corporate tax rate on corporate tax revenue. The study adopts the theory of taxation by Ibn Khaldun, depicted as the Laffer curve. Design/methodology/approach – The paper analyses time series data for the period 1996 to 2014 using the autoregressive distributed lag (ARDL) approach. Findings – The paper finds that the corporate tax rate has a dual effect on corporate tax revenue over the study period. It shows an inverted U-shape relationship between the corporate tax rate and corporate tax revenue and reveals that the optimal tax rate is 25.5156 per cent. Inferentially, a positive relationship exists between the two variables prior to the optimal tax rate, and a negative relationship prevails afterwards. A further test of causality shows a long-run unidirectional causality between corporate tax rate and corporate tax revenue. Research limitations/implications – First, it should be noted that the policy was not implemented in isolation. Several other tax incentives were given to corporate tax payers, and therefore, such incentives should be controlled for to have a more insightful evaluation of the policy. Second and most important, there is a need to investigate whether the increased cash flow available to firms as a result of the reduction in the corporate tax rate adds value to firms. It is also necessary to investigate whether firms’ stakeholders benefited from the increased cash flow or was there managerial diversion of firms’ resources. Practical implications – The policy of gradual reduction of the corporate tax rate in Malaysia is suspected to have a positive impact on the productivity of Malaysian companies, which has contributed to an increase in corporate tax revenue. It also has a positive impact on the economic growth of the country. It means that the lower corporate tax rate has actually reduced the cost of doing business in the country. Originality/value – The benefit of increased corporate tax revenue needs to be investigated empirically for insightful policy evaluation. In Malaysia, however, such investigation is close to non-existent to the best knowledge of the researchers. Thus, the present study aims at investigating the impact of the policy of gradual reduction of the corporate tax rate on corporate tax revenue over an 18-year period from 1996 to 2014.